PENGGUNAAN PERMAINAN MONOPOLI EDUKATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI MIM 1 PANTENAN - Nataria Wahyuning Subayani (JUSEDA, 2020)
Zuhrina Aulia Izzati (NIM 14 441 008) Use of Monopoly Eductive Games to Increase Student Learning Outcomes at MIM 1 Order. Guided by Dr. Irwani Zawawi and Nataria Wahyuning Subayani, M.Pd.Based on the results of interviews, teachers have not used learning media in teaching and learning activities that seem monotonous because there is no demand for students to think creatively in developing abilities and the absence of media that interests students. This study aims to describe the increase in social studies learning outcomes of class V students by applying the educational monopoly media in MIM 1 to order material figures of independence.This classroom action research uses four stages which include planning, observing, and reflecting. The subjects of this study were students of class V MIM 1, Pantenan Panceng Gresik, which numbered 22 students. Data collection methods used are observation sheets of student activities, observation sheets of teacher activities, test results of learning.Based on the results of data analysis obtained cycle 1 63.63% of students completed and as many as 36.37% of students did not complete, while the second cycle as much as 86.36% of students completed and as many as 13.64% of students who did not complete.